2018
DOI: 10.1177/1753193418758852
|View full text |Cite
|
Sign up to set email alerts
|

Activity gains after upper limb surgery for spasticity in patients with spinal cord injury

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
(31 reference statements)
1
7
0
Order By: Relevance
“…A mean of 1.4 improvements in MAS and significant improvement in resting position, improvement of the wrist, finger, and thumb passive ROM and active were reported. Wangdell et al ( 5 ) reported the result of the procedure of tendon lengthening for wrist flexors and finger flexors combined with the additional procedure of pronator teres, thumb adductor, and intrinsic tendon release if necessary, in tetraplegic, SCI patients. The most common tendons lengthened were flexor digitorum superficialis (FDS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mean of 1.4 improvements in MAS and significant improvement in resting position, improvement of the wrist, finger, and thumb passive ROM and active were reported. Wangdell et al ( 5 ) reported the result of the procedure of tendon lengthening for wrist flexors and finger flexors combined with the additional procedure of pronator teres, thumb adductor, and intrinsic tendon release if necessary, in tetraplegic, SCI patients. The most common tendons lengthened were flexor digitorum superficialis (FDS).…”
Section: Resultsmentioning
confidence: 99%
“…These manifestations of hypertonicity are the main complication in many upper motor neuron disorders, such as cerebral palsy (CP), traumatic brain injury (TBI), stroke, multiple sclerosis (MS), and spinal cord injury (SCI), with about 40% prevalence in patients after stroke ( 3 ) and 65% in patients with SCI ( 4 ). Spasticity may lead to stiffness of the affected muscles, joints, and surrounding soft tissue and ultimately contracture ( 5 ). Restricted range of motion (ROM) due to spasticity or contracture may cause pain, skin breakdown, and have a significant influence on daily activities including mobility, feeding, hygiene, and dressing.…”
Section: Introductionmentioning
confidence: 99%
“…According to the standard procedure at our centre, early active rehabilitation was applied in patients assigned to the high and medium rehabilitation levels. This promotes early active mobilization of sutured tendons and surrounding tissues and thus maintenance of ADL (Friden et al., 2010; Wangdell et al., 2016, 2018). All patients received wrapping and a custom-made splint (plaster in the low intensity group) for day and night use to prevent swelling, to maintain the length of the operated tendons and to prevent contractures.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to report and classify POPG according to ICF in a cohort of patients stratified in groups based on diagnosis, gender, and severity of UL impairment. Previous reports exist on the same theme but involve patients with disabling spasticity who are receiving botulinum toxin treatment [24,25] or are limited to patients with SCI only [26]. COPM has previously been used to demonstrate positive POPG outcomes in a mixed population undergoing spasticity-correcting surgery [12] and with patients split into regimens [13].…”
Section: Discussionmentioning
confidence: 99%